2010
DOI: 10.1103/physrevb.82.165433
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydrodynamic and Dirac models of dispersion interaction between graphene and H,He, or Na atoms

Abstract: The van der Waals and Casimir-Polder interaction of different atoms with graphene is investigated using the Dirac model which assumes that the energy of quasiparticles is linear with respect to the momentum. The obtained results for the van der Waals coefficients of hydrogen atoms and molecules and atoms of metastable He * and Na as a function of separation are compared with respective results found using the hydrodynamic model of graphene. It is shown that, regardless of the value of the gap parameter, the Di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
80
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 42 publications
(90 reference statements)
5
80
4
Order By: Relevance
“…The calculations performed in the Ref. [31] showed that the Casimir-Polder force calculated in framework the Dirac model is smaller then for hydrodynamic model. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculations performed in the Ref. [31] showed that the Casimir-Polder force calculated in framework the Dirac model is smaller then for hydrodynamic model. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Some calculations related with the Casimir and Casimir-Polder energies were made in the framework of this model in the Refs. [29,30,31]. The frequency spectrum in the hydrodynamic (plasma) model has quadratic form and the model is high-frequency approximation of the theory.…”
Section: Introductionmentioning
confidence: 99%
“…The Casimir-Polder energy of different atoms on single layer has been considered in Refs. [24,26]a n do nm u l t i l a y e rg r a p h e n ei nR e f . [ 29].…”
Section: Introductionmentioning
confidence: 99%
“…Intense theoretical effort has been devoted to the study of Casimir [11][12][13][14][15][16][17][18][19][20][21][22][23]andCasimir-Polder [23][24][25][26][27][28][29]interactionsingraphene and related systems [30,31]. The Casimir-Polder energy of different atoms on single layer has been considered in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Not even the spatial dependence of the interlayer interaction has been firmly determined, an uncertainty that raises doubts concerning the vdW interactions in graphitic systems. 29,30 The are many measurements and simulations for geometric and electronic properties that have yielded results that differ by more than 40%. [3][4][5][6][7] Many of thse properties depends on the curvature of the interlayer binding energy curve.…”
Section: Introductionmentioning
confidence: 99%